2022
DOI: 10.3389/fmed.2022.807443
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleed Automatic Detection System Based on the “Deep Learning”

Abstract: ObjectiveTo validate the reliability and efficiency of clinical diagnosis in practice based on a well-established system for the automatic segmentation of cerebral microbleeds (CMBs).MethodThis is a retrospective study based on Magnetic Resonance Imaging-Susceptibility Weighted Imaging (MRI-SWI) datasets from 1,615 patients (median age, 56 years; 1,115 males, 500 females) obtained between September 2018 and September 2019. All patients had been diagnosed with cerebral small vessel disease (CSVD) with clear cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In a comparison of automated segmentation studies ( Duan et al, 2020 ), implemented CMB segmentation in non-SWI sequences, but a DSC of only 50.30% was achieved. Fan et al (2022) implemented 3D segmentation for CMBs, but a DSC of only 72.00% was achieved. There have also been studies on brain vessels ( Dang et al, 2022 ), haemorrhage strokes ( Li et al, 2021a ) and white matter hyperintensities ( Li et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a comparison of automated segmentation studies ( Duan et al, 2020 ), implemented CMB segmentation in non-SWI sequences, but a DSC of only 50.30% was achieved. Fan et al (2022) implemented 3D segmentation for CMBs, but a DSC of only 72.00% was achieved. There have also been studies on brain vessels ( Dang et al, 2022 ), haemorrhage strokes ( Li et al, 2021a ) and white matter hyperintensities ( Li et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…They found that CMBs were significantly associated with greater WMH and lower total white matter fractional anisotropy. Additionally, researchers also applied deep learning on SWI for the CMBs segmentation in patients diagnosed with CSVD [36].…”
Section: Applications Of Deep Learning Techniques In Neuroimaging For...mentioning
confidence: 99%
“…CMBs are usually caused by CSVD (generally 2-5 mm, up to 10 mm diameter) or hemosiderin deposition in brain tissue. On imaging, CMBs manifest as round or oval scattered low signal shadows using gradient recalled echo (GRE) T2-magnetic resonance imaging (MRI) or susceptibility weighted imaging (SWI) (2,3). A 9 years follow-up study showed that CMBs did not disappear with time (4), although prevalence increased with age.…”
Section: Introductionmentioning
confidence: 99%